Perolehan Tio2 Dari Iron Ore Mengandung Titanium Melalui Proses Reduksi Karbon Dan Pelarutan Asam - Elda Rayhana; Azwar Manaf (Department of Physics, Sebelas Maret University, 2016)
REDUCTION AND LEACHING PROCESSES. Indonesia has a large source of iron ore which is quite tempting for the purposes of exploitation in form of raw materials as well as for the production of pig iron. However, not all sources of iron ore are proved useful since not only because the present of deposit is scattere dinamounts of less significant but also because it contains element of tin oxide compounds with iron like ilmenite or FeTiO3. However,ilmenite can actually be used as a source of titanium metal which is much more valuable than Fe it self. In order to recover the Ti from their respective compound it is required the release of strong bonds between the atoms in the compound. This paper reports the recovery of Ti oxide of ilmenite containing iron ore which was obtained through a combination of carbon reduction and acid leaching processes. Carbon reduction of iron ore was carried out through mechanical milling between iron ore and carbon with a ratio of 1:1. This was successively followed by a sintering at a temperature of 1000 oC employing a heating rate of 10 ° C/min for 0-3 hours. The reduction process has resulted in the formation of 27.83wt% TiO2. In order to improve the recovery level of TiO2, further reduction process was conducted through an HCl leaching. This successive stage produced fine powders in the form of deposits. Based on our quantitative analysis, the recovery of TiO2 increased to a level of 73.73%.